ETIKA PROFESI HUKUM (Dalam kajian Filsafat Hukum Islam) - Y. Sonafist (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The purpose of this research is to find out more about the ethics of the legal profession in terms of the study of Islamic philosophy and law. The research method used is qualitative with the literature method. The research results show that; 1) The ethics of the legal profession is a person's attitude in carrying out his profession as a law enforcer. 2) The code of ethics is a rule in the form of legal norms for someone to behave in accordance with their respective professions. As explained above, those included in the legal profession are the police, prosecutors, judges and lawyers. Each profession has its own code of ethics regulated by the professional organization. The Police Code of Ethics is regulated in the Regulation of the Head of the National Police of the Republic of Indonesia Number 14 of 2011 concerning the Professional Code of Ethics for the Indonesian National Police. The Prosecutor's Code of Ethics is regulated in the Attorney General's Regulation of the Republic of Indonesia Number Per–014/A/Ja/11/2012 concerning the Prosecutor's Code of Conduct. Then the Code of Ethics for Judges is regulated in the Joint Decree of the Chairman of the Supreme Court of the Republic of Indonesia and the Chairperson of the Judicial Commission of the Republic of Indonesia No. Concerning the Code of Ethics and the Code of Conduct for Judges. Finally, the Code of Ethics for Lawyers/Advocates Regulated by the Indonesian Advocates Working Committee on the Code of Ethics for Indonesian Advocates Was Ratified on May 23, 2002. 3) The problems faced by the legal profession are as follows: Quality of professional knowledge, Profession abuse, Legal profession becomes an activity business and Lack of social awareness and concern.